2014
DOI: 10.3928/01484834-20140821-12
|View full text |Cite
|
Sign up to set email alerts
|

Setting a Benchmark for the Test of Essential Academic Skills (TEAS) V: Striving for First-Semester Success in Nursing School

Abstract: Every nursing school strives to admit students who will be successful in completing their program and passing the NCLEX(®). Many schools use standardized testing, such as the Test of Essential Academic Skills (TEAS) V, as part of their admission criteria. This study was conducted to set an institutional benchmark of the TEAS V composite score, as recommended by the test developers. Having a benchmark would help the authors' school of nursing to identify students who were more likely to be successful during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…The results of this study showed that the cognitive-academic abilities of applicants are assessed mainly through academic records or standardized tests (38,47). Research evidence suggests that standardized tests and academic records are more relevant to future academic performance of nursing students than other methods (interview and non-standardized tests) (6,31,37,52,56,58,60,62), and are better predictors of nursing students' academic success (31,40). In their model for selecting medical students, Bore et al cited academic records of applicants as a prerequisite for entering the cognitive-academic ability assessment phase (71).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that the cognitive-academic abilities of applicants are assessed mainly through academic records or standardized tests (38,47). Research evidence suggests that standardized tests and academic records are more relevant to future academic performance of nursing students than other methods (interview and non-standardized tests) (6,31,37,52,56,58,60,62), and are better predictors of nursing students' academic success (31,40). In their model for selecting medical students, Bore et al cited academic records of applicants as a prerequisite for entering the cognitive-academic ability assessment phase (71).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the review results, the TEAS was the most commonly used test, yet reliability of test was only con rmed in one study (NDRT test: Nelson-Denny Reading Test) (51). The reliability or validity of other selection tests reported based on previous assessments by instrument developers in the studies (37,40,48,52,56,60,62). In other studies, the reliability and validity of the test used was not reported (31,32,35,41,42,44,50,57,58,61).…”
Section: Non-cognitive Abilitiesmentioning
confidence: 96%
“…The results of this study showed that the cognitive-academic abilities of applicants are assessed mainly through academic records or standardized tests (37,46). In order to evaluate this ability, the research evidence suggests that the standardized tests and academic records are more relevant to the future academic performance of the nursing students than the other methods (interview and non-standardized tests) (6,30,36,51,55,57,59,61), and are better predictors of nursing students' academic success (30,39). However, the ndings of this study indicated that none of the standardized tests evaluate all of the four cognitive-academic skills in one test.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the review results, the TEAS was the most commonly used test, yet reliability of test was only con rmed in one study (NDRT test: Nelson-Denny Reading Test) (50). The reliability or validity of other selection tests reported based on previous assessments by instrument developers in the studies (36,39,47,51,55,59,61). In other studies, the reliability and validity of the test used was not reported (30,31,34,40,41,43,49,56,57,60).…”
Section: Academic Achievement Recordsmentioning
confidence: 99%
“…Research article To identify potential attributes and key skills for entering the field of nursing and midwifery 502 participants survey Consensus in the top seven ranked attributes: honesty and trustworthiness, communication skills, being a good listener, patience and tactfulness, sensitivity and compassion, good team worker and the ability to seek and act on guidance. Bremner et al 2014, USA [ 55 ] Research article To identify students most likely to succeed in nursing studies using TEAS 511 first semester students enrolled from fall 2011 to fall 2013 A cross-sectional, descriptive study Test of Essential Academic Skills (TEAS) scores predicted first semester ATI proficiency Harner 2014, USA [ 56 ]. Doctoral dissertation To examine the relationship between TEAS scores and early academic success in a BSN program 218 nursing students.…”
Section: Methodsmentioning
confidence: 99%